2016
DOI: 10.1186/s40200-016-0272-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multi-country observational trial to compare the incidences of diabetic ketoacidosis in the month of Ramadan, the preceding month, and the following month (DKAR international)

Abstract: Background1.7 billion Muslims worldwide obey divine commands of fasting for a month. This may increase the probability of the acute complications of diabetes during the fasting period.Design and methodsWe primarily aimed to compare the incidences and duration of Diabetic ketoacidosis (DKA) admissions during Ramadan compared to the month before (Shaaban) and the month after (Shawal) as well as the average pre-Ramadan six months' admissions. Our secondary objective was to assess the different incidence of DKA be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…Another study revealed a substantial increment in cases of hypoglycemia during Ramadan as compared to other lunar months, particularly for insulin treated diabetics in comparison to those who use oral hypoglycemic agents (OHA). This is different from the heightened hospitalization rate and incidence caused by DKA in Ramadan with prolonged acidosis as obtained by Abdelgadir and colleagues [ 5 ]. This prospective study was conducted by major hospitals in United Arab Emirates, Sudan, Tunisia, and Morocco, involving 167 patients from lunar month before Ramadan (Shaban) until a month after fasting period (Shawal).…”
Section: Introductioncontrasting
confidence: 68%
“…Another study revealed a substantial increment in cases of hypoglycemia during Ramadan as compared to other lunar months, particularly for insulin treated diabetics in comparison to those who use oral hypoglycemic agents (OHA). This is different from the heightened hospitalization rate and incidence caused by DKA in Ramadan with prolonged acidosis as obtained by Abdelgadir and colleagues [ 5 ]. This prospective study was conducted by major hospitals in United Arab Emirates, Sudan, Tunisia, and Morocco, involving 167 patients from lunar month before Ramadan (Shaban) until a month after fasting period (Shawal).…”
Section: Introductioncontrasting
confidence: 68%
“…Singapore (17), France (18), United Kingdom (19)(20)(21)(22), Qatar (23), United Arab Emirates (24,25), Egypt (26), Lebanon (27) and Pakistan (28). Several multi-center studies were included in this review (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Eight studies were randomized controlled trials (15,16,19,27,29,34,38,39) Five studies reported on hospital admissions during Ramadan (15,18,24,31,37), but were not included in the meta-analysis due to different methods of outcome reporting.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Several multi-center studies were included in this review (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Eight studies were randomized controlled trials (15,16,19,27,29,34,38,39) Five studies reported on hospital admissions during Ramadan (15,18,24,31,37), but were not included in the meta-analysis due to different methods of outcome reporting. One study reported on the number of cases with DKA and medication adherence at two time points (37), but was not eligible as recommended by the Cochrane group, the meta-analysis should combine results from two or more separate studies (10).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…7 However, fasting can increase the risk of hypoglycemia 6,8 and diabetic ketoacidosis. 9 Further, individuals who adjust their own medications are more likely to experience severe hypoglycemia during Ramadan. 6 By comparison, individualized education during Ramadan can help Muslims with type 2 diabetes lose weight, improve glycemic control and avoid severe hypoglycemia.…”
Section: Practicetoolmentioning
confidence: 99%